Local knowledge economies, mobility perceptions and support for right-wing populist parties: New survey evidence for the case of Germany - Kattalina Berriochoa; Marius R. Busemeyer (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
The rise of knowledge economies is transforming labor markets with substantial socio-political implications. Recent literature suggests that these economies foster voters who, due to the current or potential experience of upward mobility, are less likely to support far-right parties. Using novel survey data for the case of Germany, we examine this assertion by analyzing the association between the local share of knowledge-based economic activity and individual mobility perceptions and vote choices. We find that individual mobility perceptions are - somewhat counterintuitively - more negative in thriving local knowledge economies (LKEs). We also examine how these local economic contexts and mobility perceptions explain vote choices, focusing on support for the Greens and the right-wing populist AfD, finding that electoral support for the Greens is strongly and positively associated with well-developed LKEs and less influenced by mobility perceptions, while the latter matters more in the case of support for the AfD. Yet, we also find that thriving LKEs can reinforce the impact of static mobility perceptions increasing support for the AfD. Our analysis shows that LKEs, while a sign of positive economic growth, can also lead to friction between individuals with different perceptions of mobility likely reflecting the winners and losers of technological and labor market changes at the local level.
urn:nbn:de:bsz:352-2-1vikpkh6dkklv9
Keywords: 320; Political Preferences; Inequality; Knowledge Economy; Populism; Local Context